A Foreign Language or the Second Language: The Future of English in Bangladesh - Ara, Rowshon (Universitas Negeri Makassar, 2020)
Bangladesh does not have an official second language. However, apart from Bangla, English is the only other language widely used in the country. There has been a sustained debate whether English is a foreign language (EFL) or English is the second language (ESL) in Bangladesh, for often it is found that the function of English in the country is much closer to that of the second language. English in Bangladesh had a turbulent past as well as has an undefined but overwhelming present. Due to globalization and major economic connections with the outer world the presence of English has always been there. The all-embracing state of English in Bangladesh now is undeniable. The function of English in Educational sectors, Government sectors, courts, private organizations, media and communication etc. reveal the overpowering effect of English in the lives of people in Bangladesh. As such the all obtruding impact of English in the present life posits the enquiry on the future of the language in the land. This paper is a qualitative study that analyzes the domains of language use. The results reflect an urgency of change of the official status of English in Bangladesh from a foreign language to a second language.